Association between Dysphagia and Surgical Outcomes across the Continuum of Frailty. Issue 2 (3rd July 2021) - Cohen, Seth M.; Porter Starr, Kathryn N.; Risoli, Thomas; Lee, Hui-Jie; Misono, Stephanie; Jones, Harrison; Raman, Sudha
Abstract: This study examined the relationship between dysphagia and adverse outcomes across frailty conditions among surgical patients ≥50 years of age. A retrospective cohort analysis of surgical hospitalizations in the Healthcare Cost and Utilization Project's National Inpatient Sample among patients ≥50 years of age undergoing intermediate/high risk surgery not involving the larynx, pharynx, or esophagus. Of 3, 298, 835 weighted surgical hospitalizations, dysphagia occurred in 1.2% of all hospitalizations and was higher in frail patients ranging from 5.4% to 11.7%. Dysphagia was associated with greater length of stay, higher total costs, increased non-routine discharges, and increased medical/surgical complications among both frail and non-frail patients. Dysphagia may be an independent risk factor for poor postoperative outcomes among surgical patients ≥50 years of age across frailty conditions and is an important consideration for providers seeking to reduce risk in vulnerable surgical populations.